Serum ACE2, Angiotensin II, and Aldosterone Levels Are Unchanged in Patients With COVID-19 - Rieder, Marina; Wirth, Luisa; Pollmeier, Luisa; Jeserich, Maren; Goller, Isabella; Baldus, Niklas; Schmid, Bonaventura; Busch, Hans-Joerg; Hofmann, Maike; Kern, Winfried; Bode, Christoph; Duerschmied, Daniel; et al. (American journal of hypertension, 2021)
The role of the renin-angiotensin-aldosterone system (RAAS) in coronavirus disease 2019 (COVID-19) is controversially discussed. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enters host cells by binding to angiotensin-converting enzyme 2 (ACE2) and activity of the RAAS may affect susceptibility to SARS-CoV-2 infection and outcome of patients with COVID-19. In this prospective single-center study, we determined the serum levels of ACE2, angiotensin II, and aldosterone in patients with COVID-19 compared with control patients presenting with similar symptoms in the emergency unit. We analyzed serum samples from 24 SARS-CoV-2 positive and 61 SARS-CoV-2 negative patients. SARS-CoV-2 positive and control patients did not differ in baseline patients characteristics, symptoms, and clinical presentation. Mean serum concentrations of ACE2, angiotensin II, and aldosterone did not differ between the SARS-CoV-2 positive and the control group. In line with this, serum potassium as surrogate parameter for RAAS activity and blood pressure were similar in both groups. In summary, we did not find evidence for altered RAAS activity including angiotensin II, aldosterone, or potassium levels, and blood pressure in patients with COVID-19. Trial Number DRKS00021206.